Lane-change detection based on individual driving style. (18th October 2019) - Woo, Hanwool; Ji, Yonghoon; Tamura, Yusuke; Kuroda, Yasuhide; Sugano, Takashi; Yamamoto, Yasunori; Yamashita, Atsushi; Asama, Hajime
ABSTRACT: This paper presents a novel method to detect when a vehicle is changing lanes by considering individual driving styles. Some previous works have focused on the relation between lane changes and driving styles; however, the detection method of lane changes while considering driving styles is still not reported. The proposed method extracts a new feature to appropriately describe driving styles based on drivers' risk taking behavior when following the preceding vehicle. Based on the driving style of the target vehicle, performing a lane change is estimated at each time step. The determined driving style is used as input for the lane-change detection method based on the gap acceptance model, and it is integrated with the detection method based on vehicle movements. Experiments are used to demonstrate that the proposed method considerably improves detection performance. GRAPHICAL ABSTRACT: